Women’s perceptions of support system for leadership development/ Agnes Paulus Jidwin ... [et al.] - Jidwin, Agnes Paulus; Mohammed, Rozita @ Uji; Stephen, Jacqueline Koh Siew Len; Tajuddin, Dewi; David, Jasmine (Universiti Teknologi MARA, Sabah, 2024)
This empirical study investigates various forms of support systems designed to foster women's leadership in Sabah, Malaysia. Data was collected through a survey questionnaire from a sample of 282 professional women working in Sabah's public and private sectors. The research evaluates the existing support mechanisms and analyses gender sensitivity and pathways for women to assume leadership positions. Using quantitative analysis, the study assesses the effectiveness of support systems for leadership development, including training programs, study leave incentives, equal opportunities provisions, gender sensitivity initiatives, governance structures, and the Sustainable Development Goals (SDG) 5 and SDG 8 agenda. The findings reveal a nuanced view of the support systems available to women in Sabah. Respondents acknowledged the presence of initiatives promoting gender equality and supporting women's advancement within organisations. However, the analysis indicates that these support systems are insufficient in addressing the diverse needs of women in Sabah's professional environment.